TiO2 rutile–anatase core–shell nanorod and nanotube arrays for photocatalytic applications - Pan, Lei (2013)
Rutile and anatase mixed TiO2 is a promising material for photocatalytic applications. In this work, rutile–anatase core–shell nanotube (NT) and nanorod (NR) structures were fabricated directly on a fluorine doped SnO2 (FTO) glass substrate using a hydrothermal growing/etching and TiCl4 post-treatment method. A pure rutile phase NT/NR core was coated with a roughened anatase shell. The nanostructures were characterized using scanning electron microscopy, transmission electron microscopy, X-ray diffraction, UV-vis reflectance and transmittance spectra. The photocatalytic capability was measured by investigating the speed of methyl blue degradation UV. The core–shell NT structure showed superior photocatalytic properties due to larger light absorbing areas, higher light trapping capability and enhanced charge separation efficiency.